Driving consistency: CEPI-Centralized Laboratory Network's conversion factor initiative for SARS-CoV-2 clinical assays used for efficacy assessment of COVID vaccines - Ali Azizi; Gathoni Kamuyu; Deborah Ogbeni; Philipa Levesque-Damphousse; Daniel Knott; Luc Gagnon; Steven Phay-Tran; Bethan Hussey; Pamela Proud; Sue Charlton; Carolyn Clark; Valentina Bernasconi (Taylor & Francis Group, 2024)
ABSTRACTTo date, thousands of SARS-CoV-2 samples from many vaccine developers have been tested within the CEPI-Centralized Laboratory Network. To convert data from each clinical assay to international standard units, the WHO international standard and the CEPI standard generated by the Medicines and Healthcare products Regulatory Agency were run in multiple facilities to determine the conversion factor for each assay. Reporting results in international units advances global understanding of SARS-CoV-2 immunity and vaccine efficacy, enhancing the quality, reliability, and utility of clinical assay data.